Mapping Evidence Syntheses in the Humanitarian Sector: Insights and Challenges (Tufts Archival Research Center, 2018)
Mapping Evidence Syntheses in the Humanitarian Sector: Insights and Challenges, by Kristin Bushby and Roxanne Krystalli